Recursos através dos ecossistemas: insetos aquáticos emergentes subsidiam comunidade de aranhas ripárias - Recalde Ruiz, Fátima Carolina [UNESP] (2014)
It is widely known that input of allochthonous subsidies in recipient food webs directly participate in the dynamics of consumers and indirectly on predator-prey interactions. However, this knowledge is based on studies from temperate forests, thus there is still a gap in the knowledge of tropical systems where the abundance and diversity of terrestrial prey is high. In this study, we investigate the effects of emergent aquatic insects on predator-prey dynamics of tropical terrestrial food webs. To test this effect, we excluded allochthonous aquatic insects using greenhouse type exclosures, and allowed emergence of insects through unmanipulated stream reaches using a randomized design. Emergent aquatic insects and terrestrial flying insects were collected through sticky traps. Terrestrial arthropods in shrubs and ground were collected manually in nocturnal and diurnal surveys, and were classified in predators, phytophages, detritivores and omnivores. The abundance of aquatic insects was five times lower in exclosures than control, but there was no effect of treatment on abundance of terrestrial fly insects; abundance of terrestrial insects were three times more abundant that aquatic insects. PERMANOVA revealed that abundance of terrestrial predators, but not their biomass, was affected by exclosure treatment. Univariate analysis show that only 11.5% of predatory taxa (Anyphaenidae, Araneidae and Theridiidae) decreased its abundance in exclosure treatment and only 7.7% of them (Araneidae and Theridiidae) decreased its biomass. Abundance of phytophages, detritivores and omnivores was not affected by treatments, but the biomass of phytophages increased six times in exclosure treatment. Despite the abundance and biomass of only few predators were affected by exclosure, we observed that predators overall derived more than 80% of N and C of aquatic prey. Our results demonstrate that allochthonous subsidies participate on terrestrial food web ...